Recreating the forest: successful examples of ethnoconservation among Dayak groups in central West Kalimantan - Jong, W. de (1995)
This chapter compares forest gardens among Dayak indigenous farmers in West Kalimantan, Indonesia. It provides a detailed analyses of 5 plots of “tembawang” forest. Tembawang are forest that are “recreated” on land that was used before as agricultural land. Dayak farmers as arule reserve certain areas of their farm land to grow tembawang, and their vegetation consists of planted species and natural regenerating forests. Although the primary forest plots show higher species diversity and more complex structure, the tembawang plots have flora richness and structure that are much close to natural forest than to other types of plantation forests.